Der modifizierte Uvulalappen zur Therapie schlafbezogener Atmungsstörungen - Hörmann, Karl; Erhardt, Thomas; Hirth, Kristine; Maurer, Joachim T. (HNO, 2001)
Background, objective. Velopharyngeal incompetence is a well described complication of uvulopalatopharyngoplasty (UPPP) for snoring or obstructive sleep apnea. A new uvulopalatal flap technique (UPF), first presented by Powell in 1996 was now modified by our team. The new technique intends to lateralize the posterior faucial pillars as the UPPP, entirely sparing uvulopalatal muscles. Results. No statistical difference existed in change of AHI before and after surgery in all patients even though 14 patients had a statistically significant decrease in AHI (pre 19,2±19,6; after 8,2±9,8; p<0,05). Snoring decreased clearly (p<0,05) from 49,4% to 25,9%.